Psychosocial Burden Due to Acne Vulgaris Affects Treatment-Seeking Behavior in Medical Students in Jakarta, Indonesia - Franklind Matthew; Regina Regina; Inneke Jane Hidajat; Melyawati Melyawati (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Acne vulgaris (AV) is a chronic inflammation of the pilosebaceous unit of the skin that occurs in 85% of adolescents and can continue into adulthood. The skin of the facial area has an essential role in socializing, therefore, facial AV can contribute to the accumulation of psychosocial stress. The prevalence of individuals with AV seeking treatments is low in some countries. This study aimed to determine the association between psychosocial burdens due to AV and medical treatment-seeking behavior in young adults. Methods: A cross-sectional study was conducted in February 2020 among 100 medical students with AV. The ASEAN Lehmann criteria were used to objectively assessed AV. Psychosocial burden was determined by the Cardiff Acne Disability Index (CADI) questionnaire and then classified into unaffected (score 0), mild (score 1-5), moderate (6-10), and severe (11-15). History-related AV was obtained through a questionnaire. The analysis was performed using the chi-square test.Results: Of the 100 medical students with AV, 82% had suffered from mild to severe psychosocial burdens. The mean score of the CADI was 4.03. However, only 44% of students sought treatment from doctors for their AV. There was a significant association between psychosocial burden and medical treatment-seeking behavior (p = 0.014).Conclusion: The psychosocial burden of acne vulgaris in young adults is high, however, medical treatment-seeking behavior is low. Therefore, psychosocial management is an essential aspect in treating patients with AV.